SEMANTIC CLASSIFICATION OF SPEECH VERBS IN UZBEK AND COMMUNICATION VERBS IN ENGLISH - Otaboeva Mazmuna Rakhimovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the formation of graduonymic series of speech verbs in the Uzbek language and communication verbs in English. It highlights various semantic groups to which these verbs belong and provides illustrative examples. Several lexemes from the speech and communication verb category are analyzed, accompanied by explanations of their synonyms and antonyms. Based on these analyses, corresponding graduonymic series have been developed.